Hubungan Paritas dan Usia Ibu dengan Kejadian Berat Badan Lahir Rendah di Rumah Sakit Umum Bali Royal Hospital Â - Ni Kadek Mila Artini; Ni Luh Putu Sri Erawati; Asep Arifin Senjaya (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2023)
Infant Mortality Rate is the main problems facing the world, because the success of health services can be measured and determined based on the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). The purpose of the study was to determine the relationship between parity and maternal age with the incidence of low birth weight at Bali Royal General Hospital in 2021. This type of research was an analytical correlation study using a cross sectional approach. The study was conducted in April-May 2022 using a non-probability sampling technique with the type of purposive sampling. The sample size used is 48 respondents. Data collection by taking data on the mother's age, parity, diagnosis and birth weight of the baby from the register or medical record. Analysis of the relationship between parity and LBW data using the coefficient contigency and analysis of the relationship between age and the incidence of LBW using chi-square. The results of the study were large respondents were mothers with moderate risk (58.3%), 95.8% low parity, as many as 29.2% occurred LBW. The conclusion is that there is no relationship between parity and the incidence of LBW infants at Bali Royal Hospital in 2021 with a p value of 0.081, there is a relationship between maternal age and the incidence of infant birth weight at Bali Royal Hospital in 2021 with a p value of 0.000. For research sites to provide more information and education to prospective pregnant women and pregnant women about the dangers of LBW risks.